Analysis of engineering structures - Bedenik, Branko S. (Horwood engineering science series., 1999)
This text delivers a fundamental coverage for advanced undergraduates and postgraduates of structural engineering, and professionals working in industrial and academic research. The methods for structural analysis are explained in detail, being based on basic static, kinematics and energy methods previously discussed in the text. A chapter deals with calculations of deformations which provides for a good understanding of structural behaviour. Attention is given to practical applications whereby each theoretical analysis is reinforced with worked examples. A major industrial application consisting of a simple bridge design is presented, based on various theoretical methods described in the book. The finite element as an extension of the displacement method is covered, but only to explain computer methods presented by use of the structural analysis package OCEAN. An innovative approach enables influence lines calculations in a simple mannger. Basic algebra given in the appendices provides the necessary mathematical tools to understand the text. Provides an understanding of structural behaviour, paying particular attention to applications, and reinforces theoretical analysis with worked examplesDetails the methods for structural analysis, based on basic static, kinematics and energy methods.